2015
DOI: 10.1111/jphp.12465
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica-based dosage forms improve release characteristics of poorly soluble drugs: case example fenofibrate

Abstract: Further experiments to determine whether the highly positive effects on fenofibrate release observed with the silica prototypes investigated to date can be translated to further poorly soluble drugs and to what extent they translate into improved in-vivo performance are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Such systems have a wide range of applications, including: tissue engineering, catalysis, chromatography, adsorbents in environmental modelling and drug delivery systems for poorly soluble APIs . For the latter, it has been widely reported that mesoporous silica can act as a solubility enhancer by ‘trapping’ API in non‐crystalline form within the mesoporous network …”
Section: Lipophilicity and Hydrophobicity Regarding Different Formulamentioning
confidence: 99%
See 1 more Smart Citation
“…Such systems have a wide range of applications, including: tissue engineering, catalysis, chromatography, adsorbents in environmental modelling and drug delivery systems for poorly soluble APIs . For the latter, it has been widely reported that mesoporous silica can act as a solubility enhancer by ‘trapping’ API in non‐crystalline form within the mesoporous network …”
Section: Lipophilicity and Hydrophobicity Regarding Different Formulamentioning
confidence: 99%
“…Finally, the solvent is removed, which can be achieved using a number of methods including vacuum drying, spray drying, lyophilisation or rotary evaporation . The second approach, incipient wetness, involves the steady addition of small volumes of concentrated API solution onto the silica, so the full amount of solvent is adsorbed into the network and then rapidly evaporated, which leaves the API within the pores . Both methods result in an API‐loaded silica, in which the previously crystalline API is now amorphous or molecularly dispersed.…”
Section: Lipophilicity and Hydrophobicity Regarding Different Formulamentioning
confidence: 99%
“…Fenofibrate silica formulations were prepared by the solvent impregnation method according to a previously published method . Briefly, a measured amount of fenofibrate was dissolved in acetone and added dropwise to the silica powder to ensure even spreading of the drug solution on the silica while avoiding excessive wetting and aggregation .…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism by which these excipients prevent crystallisation is by interacting with drug molecules and thus precluding nucleation, which is a prerequisite to precipitation. Examples of polymeric precipitation inhibitors include polyvinylpyrrolidine (PVP), hydroxypropylmethyl cellulose (HPMC), hydroxypropylmethyl cellulose acetate succinate (HPMCAS) and copovidone (PVPVA) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation